Synthesis of Hydroxyapatite/Collagen Bone-Like Nanocomposite and Its Biological Reactions - Kikuchi, Masanori; Koyama, Yoshihisa; Edamura, Kazuya; Irie, Atsushi; Sotome, Shinichi; Itoh, Soichiro; Takakuda, Kazuo; Shinomiya, Kenichi; Tanaka, Shigeo (IntechOpen, 2011)
None